Lassa Virus Infection: a Summary for Clinicians. (June 2022) - Raabe, Vanessa; Mehta, Aneesh K; Evans, Jared D.; ,; Beitscher, Adam; Bhadelia, Nahid; Brett-Major, David; Cieslak, Theodore J; Davey, Richard T; Evans, Jared D; Frank, Maria G; Iwen, Peter; et al.
Highlights: Lassa fever causes high mortality in humans, but disease signs and symptoms are nonspecific. Lassa virus spreads via contact with infected humans or rodent excreta. Optimal clinical tests for Lassa virus infection vary with the stage of infection. Two antivirals may confer benefit when used early for Lassa fever treatment. Lassa vaccines are in development, but they have not been widely studied in humans. Abstract: Objectives: This summary on Lassa virus (LASV) infection and Lassa fever disease (LF) was developed from a clinical perspective to provide clinicians with a condensed, accessible understanding of the current literature. The information provided highlights pathogenesis, clinical features, and diagnostics emphasizing therapies and vaccines that have demonstrated potential value for use in clinical or research environments. Methods: We conducted an integrative literature review on the clinical and pathological features, vaccines, and treatments for LASV infection, focusing on recent studies and in vivo evidence from humans and/or non-human primates (NHPs), when available. Results: Two antiviral medications with potential benefit for the treatment of LASV infection and 1 for post-exposure prophylaxis were identified, although a larger number of therapeutic candidates are currently being evaluated. Multiple vaccine platforms are in pre-clinical development for LASV prevention, but data from human clinical trials are not yet available. Conclusion: We provide succinct summaries of medical countermeasures against LASV to give the busy clinician a rapid reference. Although there are no approved drugs or vaccines for LF, we provide condensed information from a literature review for measures that can be taken when faced with a suspected infection, including investigational treatment options and hospital engineering controls.